Clinical Holistic Medicine: Developing from Asthma, Allergy, and Eczema - Søren Ventegodt; Mohammed Morad; Joav Merrick (The Scientific World Journal)
This paper shows how consciousness-based holistic medicine can be used in the case of asthma, allergy, and eczema. We have many fine drugs to relieve patients from the worst of these symptoms, where many children and adults suffer health problems related to hyper-reactivity of the immune system. Many symptoms remain throughout life because the drugs do not cure the allergy and allergy today is the sixth leading cause of chronic illness. The etiology of the immune disturbances is mostly unknown from a biomedical perspective. Consciousness-based holistic medicine could therefore be used to treat these diseases if the patient is willing to confront hidden existential pain, is motivated to work hard, and is dedicated to improve quality of life, quality of working life, and personal relationships. Improving quality of life is not always an easy job for the patient, but it can be done with coaching from the physician. An increased physical health is often observed after only a few sessions with a physician skilled in using holistic medical tools and able to coach the patient successfully through a few weeks of dedicated homework. Children with allergy and asthma can also be helped if their parents are able to do work on personal development, to improve the general quality of life in the family and their relationship with the child.